(untitled) (The International Journal for Scientific Research, 2025)
The primary objective of this research is to determine the relationship between asset structure, earnings per share, and investment efficiency in Saudi joint stock companies by analyzing the financial reports and statements of a sample of 41 companies for the period 2018-2022 using panel data. The researcher used the inductive approach and the quantitative analytical approach to achieve this goal. The research concluded that there is an inverse relationship between asset structure and both earnings per share and investment efficiency. There is a direct relationship between earnings per share and investment efficiency. Both asset structure and earnings per share have a significant impact on investment efficiency. The research recommended several recommendations, including that Saudi joint stock companies determine the optimal size of the asset structure and utilize it efficiently to increase both earnings per share and investment efficiency. It also recommended that they periodically study and evaluate the asset structure to ensure its suitability for their business.